Field Programmable Gate Array (FPGA)-based Intelligent Management System for Home Appliances - Maimun, Huja Husin; C. H., Kaan; Mohamad Faizrizwan, Mohd Sabri; Nurdiani, Zamhari; Asrani, Lit (2011)
This project reviews the implementation of FPGA-based system design on common home appliances in order to achieve energy efficient usage on the appliances. There are many existed method on this subject in the real world. One common method is using the Pulse Width Modulation (PWM) to control the motor speed of the home appliances. In this project, an energy saving home automation was designed using the Quartus II software. The design included a security system, curtain controller, lighting controller and a PWM generator. Security system provides protection to the house. Curtain controller and lighting controller were designed to save electricity and at the same time maintain the house in the bright condition. PWM generator was designed to optimize the air-conditioner and thermostat usage and thus save energy. Not only this system has energy saving feature but it also provide security to the users. At the end of this project, the design has successfully implemented and tested using FLEX10k chip on LP2900 board. The real implementation on hardware has not been done yet but theoretically it is proven that the designed system can save electricity.